Potential use of graphene oxide as an engine oil additive for energy savings in a diesel engine - Çetin, Ö.; Can, Ö. (Engineering Science and Technology, an International Journal, 2023)
This study investigates the effects of graphene oxide (GO) nanosheets as an engine oil additive in fully synthetic SAE 10W-40 engine oil. GO concentrations in 0.5, 1.0, 1.5, and 2.0 mg/mL were added. The viscosity index (VI) increased by up to 7 % and thermal conductivity by 4–15 %. Tribological tests with a ball-on-disc mechanism showed that 1.5 mg/mL GO nanosheets additive gave the best results in reducing the coefficient of friction (COF) by 17 % and the total wear mass loss by 44 % on average. Based on the engine friction tests on the dynamometer, GO nanosheets reduced motored torque by up to 6 %, which represents the engine frictional losses, and improved mechanical efficiency by up to 2.8 % at certain engine speeds. An average improvement of 2.6 % in brake-specific fuel consumption (bsfc) and 2.7 % in brake thermal efficiency (bte) was observed across all engine speeds. The results of detailed engine tests suggest that the GO nanosheets additive has the potential to enhance the mechanical efficiency of internal combustion engines, leading to energy and fuel savings and indirectly contributing to reducing CO2 emissions. © 2023 Karabuk University Pamukkale Üniversitesi, PAÜ This research was conducted as part of the 2019FEBE035 project funded by the Pamukkale University Scientific Research Council, in association with the master thesis of Özgür Çetin. Therefore, the authors would like to thank Pamukkale University. Additionally, the authors are also very grateful to Assoc. Prof. Dr. Erkan ÖZTÜRK for his assistance; Prof. Dr. Cem GÖK for the preparation of additives with oleic acid; Assoc. Prof. Dr. İsmail OVALI for allowing use of the pin-on-disc tribometer; Prof. Dr. Nazım USTA for conducting viscosity measurements; Prof. Dr. Sami Gökhan ÖZKAL for providing access to the thermal conductivity test apparatus; Prof. Dr. Numan B. BEKTAŞ and Res. Asst. İnan AĞIR for allowing use of the ultrasonic mixer device.